"This Feminine Scholar": Belle da Costa Greene and the Shaping of J.P. Morgan's Legacy. (3rd April 2017) - Gennari-Santori, Flaminia
Abstract : During the 1910s, Belle da Costa Greene (1879–1950), the personal librarian of John Pierpont Morgan (1835–1913), and later the major force behind the establishment of the Morgan Library as a public institution, became a key player in the international art world. Her personal history was rather extraordinary: she was an African American woman who refashioned her identity as a white person and while still in her twenties she became the closest advisor and confidante of Morgan, one of the world's most powerful men. In my article, I analyze the role that Greene played in the complex web of people and interests that revolved around Morgan's collecting enterprise. The dominant historical perspective on the art world has favored individual figures rather than the webs of players and mediators whose role was to create these networks. By focusing on Greene's professional practices and strategies, my goal is to shed light on the "mediator" as a prominent actor of the early twentieth-century art world.